Hubungan Tingkat Pengetahuan dan Sikap dengan Partisipasi Masyarakat dalam Pengelolaan Bank Sampah Berbasis Masyarakat di Kelurahan Semarapura Klod - I Nyoman Sujaya; NI Made Putri Oktaviani; I Wayan Jana; I Made Bulda Mahayana (Jurnal Kesehatan Lingkungan (JKL), 2022)
Rubbish is something no used , used , liked or something thrown away that came from from activity human . Management rubbish in Indonesia done with method subtraction and handling trash . Wrong the only one is with the Waste Bank program . Objective from study this is for know connection level knowledge and attitude with participation public in waste bank management in Ward Semarapura Klod . Study this survey with _ design cross sectional. Sample study this is 86 people taken _ by random . Data collected use sheet Interview then analyzed with chi square test . Results chi square test obtained from connection level knowledge with participation community p 0.000 a ( 0.05 ) CC value 0.590 and chi square test is obtained from attitude customer with participation community p 0.000 a (0.05) CC value 0.644 which means there is connection level knowledge and attitude with participation public in waste bank management . Knowledge and attitude customer need improved , hope also Waste Bank Manager and Public health center local To do counseling socialization about waste bank management so that participation public in waste bank management could increase